Modelo de gestión operativa Lean y su impacto en la satisfacción de los clientes en la Agencia BCP Mercado Mayorista 2013-2014. - Noriega Barrera, Sissy Vivien (2016)
This thesis makes an analysis on the use of the management model LEAN and how it has influenced the satisfaction of customers and users of BCP Agency Wholesale Market, in order to know which factors influence the development of our quality of care for customer satisfaction. It is known that the Banco de Credito Del Peru applies the technique of measuring quality through surveys its customers since 2013, to measure the level of satisfaction with the quality of customer care in all business segments of the bank. Regarding the results of the surveys customers of Banco de Credito Del Peru (BCP) in the agency BCP Wholesale Market, it was obtained as a general value of 85% (100), which indicates greater satisfaction customer in terms of satisfaction as an agency. It is also managed-successful now through the 4 axes set by the bank, with efficient growth of 93.8%, the customer improved significantly in all service channels, passing the finish line and exceeding the minimum grade quality. Implementing management model Lean has improved the efficiency of BCP Agency Wholesale Market since productivity between 34% increase compared to the results obtained in the previous year, also in reducing waiting times customer in more than 63% compared to 2011.